Records Of The Colony Of New Plymouth In New England. Boston, 1861 Page 66, Image 77 - (:unkn) unknown (General Publisher, 1656)
Laws of Plymouth Colony (1656). And likewise that no Indian shall discharge any gun on the Lords day at any thing to the breach of the Sabbath and disturbance of the English; as they will answer it at their peril.
--
Keywords: DISCHARGE